2016
DOI: 10.3390/agronomy6010008
|View full text |Cite
|
Sign up to set email alerts
|

Agro-Morphological Evaluation of Rice (Oryza sativa L.) for Seasonal Adaptation in the Sahelian Environment

Abstract: Abstract:In the Sahel zone of West Africa that extends from Senegal to Chad, temperatures can vary from less than 15˝C to 25˝C from November to February. These low temperatures affect the growth, development and yield of rice plants, and therefore constitute a major constraint to rice production in the Sahel. In order to identify rice varieties tolerant to cold stress at different developmental stages, a diverse set of 224 rice germplasm was evaluated for yield and yield-related traits in Ndiaye, Senegal, usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
2
5
1
Order By: Relevance
“…Lower tiller number was exhibited under stressed conditions suggesting that cold stress affected tillering ability. Similar result were obtained Shimono et al (2007) and Ndour et al (2016) who reported that low temperature at seedling stage reduced tillering ability.…”
Section: Discussionsupporting
confidence: 89%
“…Lower tiller number was exhibited under stressed conditions suggesting that cold stress affected tillering ability. Similar result were obtained Shimono et al (2007) and Ndour et al (2016) who reported that low temperature at seedling stage reduced tillering ability.…”
Section: Discussionsupporting
confidence: 89%
“…The number of days-to-flowering was found to have a moderate positive correlation to the number of tillers (r=0.372; p<0.01) and panicles per plant (r=0.345; p<0.01) since the number of tillers was positively correlated to the number of panicles (r=0.965; p<0.01). A similar trend was observed for the days-to-mature and the tiller number (r=0.470) when 224 rice accessions with different origins were evaluated at a research station of the Africa Rice Centre under the Sahelian environment (Ndour et al, 2016). In addition, a study by Seo et al (2018) on 87 rice accessions from six countries found that days-to-50% flowering and days-to-80% maturity were positively correlated with tiller number and panicle number.…”
Section: Factors Affecting Yield Of Lowland Rice Varietiessupporting
confidence: 65%
“…In this study, the early maturing genotypes with high yield were IVT.1M(H)-2817, IURON-20, IURON-8, IURON-10, IRTON-23 and IRTON-25. Also (Ndour et al, 2016;Ranaweke et al, 2014) found that early maturing genotypes were more adapted to temperate climatic conditions than late late maturing ones because low temperature affects the growth, development and yield of rice plant and constitute a major constraint to rice production.…”
Section: Resultsmentioning
confidence: 99%